Disparity in VUK Ratio Achievement against GDP among Provinces in Indonesia: Target Gap Analysis and Regional Quadrant Mapping - Asmar Asmar; Adriansyah; Yulia Yunita Yusuf; suharti Sirajuddin; Andi Nurrahma Gaffar (PT ARRUS Intelektual Indonesia, 2026)
This study aims to analyze disparities in the achievement of the VUK-to-Gross Regional Domestic Product (GRDP) ratio across provinces in Indonesia through target-achievement gap analysis and regional quadrant mapping. This study employs a descriptive-evaluative quantitative approach using secondary data from 38 provinces in Indonesia. The analysis covers historical data from 2020 to 2024, target and achievement data from 2025 to 2026, and target/projection data from 2027 to 2029 as a policy context. The analytical techniques include descriptive statistics, trend analysis, gap analysis, ranking analysis, and quadrant mapping. The results show that the national VUK-to-GRDP ratio declined from 1.10 in 2020 to 0.97 in 2024. National achievement also remained below the target, with a gap of -0.08 in 2025, widening to -0.13 in 2026. At the provincial level, substantial disparities were observed. Several provinces, including East Nusa Tenggara, West Kalimantan, Central Java, East Kalimantan, and South Sulawesi, recorded positive gaps in 2025, while Papua Highlands, Central Papua, South Papua, Papua, and Bali recorded the largest negative gaps. The 2025 quadrant mapping shows that 13 provinces are classified as leading regions, 6 as potential regions, 6 as under-optimized regions, and 13 as priority intervention regions. These findings indicate that policies to improve the VUK-to-GRDP ratio should be designed based on regional characteristics rather than a uniform national approach. This study contributes by integrating trend analysis, target-achievement gap analysis, and regional quadrant mapping as a basis for evaluating interprovincial disparities.